Voice/Body/Skin: (Dis)locating Belonging in Antjie Krog's Country of My Skull, A Change of Tongue, and Begging to Be Black. (2nd January 2018) - Scott, Claire
ABSTRACT: In this article I seek to reflect on the progression of Antjie Krog's use of the tropes of "the voice", "the body", and "the skin" over the course of her three literary journalism texts, Country of My Skull (2002), A Change of Tongue (2004), and Begging to Be Black (2009). I use the term "literary journalism" to foreground the generic instability of Krog's texts, which weave together journalism, memoir, travel writing, social commentary, the poetic, and fictional elements. In Krog's writing, the form, style, and structure of her texts are as important in the process of creating meaning as her language choices and content. By writing at the messy, contested border between literature and journalism, Krog is able to explore the intangible and affective aspects of identity and belonging. I conclude by suggesting that, as Krog moves from a preoccupation with "the voice" and "the body" to the concept of "skin", she is able to draw on the notion of the "in-between" to address her most pressing concerns surrounding questions of white identity and national belonging.